2004
DOI: 10.1080/13594320444000164
|View full text |Cite
|
Sign up to set email alerts
|

Charismatic leadership, environmental dynamism, and performance

Abstract: Most studies relating charismatic leadership to performance have limitations concerning selection of criterion measures and investigation of moderators. Therefore, this study examines relationships between charismatic leadership and multiple performance outcomes under different levels of environmental dynamism (i.e., level of environmental uncertainty, degree of technological change) and per type of Chief Executive Officer (firm owner versus managing director). Results revealed that charismatic leadership was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
86
3
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(94 citation statements)
references
References 61 publications
3
86
3
2
Order By: Relevance
“…For example, Waldman et al (2001) found that the relationship between CEO charismatic leadership and firm financial performance was positive, but this only held when environmental conditions were uncertain and changeable. Also, De Hoogh et al (2004b) found that the relationship between charismatic leadership and subordinates' positive work attitude to be stronger in such uncertain, unpredictable environments. As stated, we see a dynamic environment as a relatively uncertain situation, characterized by a high degree of challenge and great opportunities for change.…”
Section: Charismatic Leadership Transactional Leadership and Effectimentioning
confidence: 96%
See 1 more Smart Citation
“…For example, Waldman et al (2001) found that the relationship between CEO charismatic leadership and firm financial performance was positive, but this only held when environmental conditions were uncertain and changeable. Also, De Hoogh et al (2004b) found that the relationship between charismatic leadership and subordinates' positive work attitude to be stronger in such uncertain, unpredictable environments. As stated, we see a dynamic environment as a relatively uncertain situation, characterized by a high degree of challenge and great opportunities for change.…”
Section: Charismatic Leadership Transactional Leadership and Effectimentioning
confidence: 96%
“…Other researchers have investigated slightly different concepts in relation to charismatic leadership, for example environmental uncertainty (cf. De Hoogh et al, 2004b;Flynn & Staw, 2004;Waldman et al, 2001) crisis (cf. Pillai, 1996;Pillai & Meindl, 1991) and technological change (cf.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…They display self-confidence and are able to inspire followers to transcend their own self-interest for the sake of the collective (e.g., Bass, 1985;House, 1977House, , 1996Shamir, House, & Arthur, 1993). Meta-analyses have shown that charismatic leadership correlates positively with a wide range of variables (e.g., Fuller, Patterson, Hester, & Stringer, 1996;Lowe, Kroeck, & Sivasubramaniam, 1996), including organizational commitment (e.g., Bycio, Hackett, & Allen, 1995), personal identification (Shamir, Zakay, Breinin, & Popper, 1998), and firm profitability (e.g., De Hoogh et al, 2004;Waldman et al, 2001). Previous research has also suggested that charismatic leadership elicits OCB from followers.…”
Section: Charisma and Belongingnessmentioning
confidence: 99%
“…For example, De Hoogh et al (2004) found that the relationship between charismatic leadership and subordinates' positive work attitude was stronger in uncertain, unpredictable environments. In such a context, charismatic leaders can more easily generate appeal for their vision (Trice & Beyer, 1986;Waldman et al, 2001).…”
Section: Charisma and Belongingnessmentioning
confidence: 99%
See 1 more Smart Citation